Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Kacamata Di Alun-Alun Kota Surakarta - Wulandari, Oryz Agnu Dian, Drs. M. Nasir, M.M (2015)
The background of this research by many diverse and thriving business, one optical glasses effort. Increasingly banyaknnya sellers who are interested in the optical business, so the more sellers who are interested in moving in the same field. This study aimed to examine the effect of a variable price, location and income on consumer purchasing decisions glasses at Town Square Surakarta. After review of the literature and formulation of hypotheses, data were collected through questionnaires to 110 buyers of glasses in Alun-AlunKota Surakarta obtained using random sampling techniques. Then conducted an analysis of the data obtained by quantitative data. Quantitative analysis includes: validity and reliability, the classic assumption test, multiple linear analysis, hypothesis testing via t test and F, as well as the analysis of the coefficient of determination (R2). The data that has met the validity, reliability and classical assumption processed using SPSS (Statistical Package for Social Science) for Windows 17 so as to produce a regression equation as follows: Y = 0.49 + 0.344 X1 + 0.668 X2 X3 Where the consumer purchase decision variable (Y), quality price (X1), the location (X2), income (X3). Hypothesis testing using t test showed that the price variable but not significant positive effect on purchase decisions. While the location and income variables significantly influence purchasing decisions. Then through the F test can be seen well-deserved three independent variables to test the dependent variable consumer purchasing decisions. Figures Adjusted R Square of 0.402 indicates that 40.2% percent of consumer purchasing decisions variation can be explained by the three independent variables in the regression equation. While the remaining 59.8 percent is explained by other variables outside the three variables used in this study. Keywords: consumer purchasing decisions, price, location and income.